Personal Branding Danise Julia Franchise Ratag melalui Akun Instagram @Danisefrnc - Anggieta Salsabilla; Yuliant (Bandung Conference Series: Public Relations, 2024)
Abstract. The rapid development of internet technology and the popularity of social media, especially Instagram, have created a vast market for personal branding. This phenomenon has led to intense competition among influencers, where individuals strive to build unique and appealing personal brands to attract and maintain loyal followers on social media platforms, particularly Instagram. This research aims to measure the authenticity, integrity, consistency, specialization, relevance, visibility, persistence, and goodwill of Danise Julia Francise Ratag's personal branding. A descriptive quantitative method was employed, distributing an online questionnaire to her followers, with a total of 100 respondents. The sampling technique used was purposive sampling. Data analysis utilized SPSS to measure these variables and provide insights for individuals interested in building personal brands through Instagram. The findings indicate that Danise has successfully built an authentic personal brand aligned with her identity on social media, maintaining integrity and consistency in conveying values relevant to the fashion industry. Her content is deemed relevant to current trends and has a strong positive impact on her followers. Danise effectively manages her visibility on Instagram through strategic use of hashtags and collaborations, while consistently creating high-quality content that supports intensive interaction with her followers. The implications of this research underscore the importance of optimizing personal branding strategies on Instagram. Abstrak. Perkembangan pesat teknologi internet dan popularitas media sosial, terutama instagram menciptakan pangsa pasar besar bagi personal branding. Fenomena yang terjadi di lapangan adalah adanya kompetisi yang ketat di kalangan selebgram, di mana setiap individu berusaha membangun personal branding yang unik dan menarik untuk menarik perhatian dan membangun pengikut yang loyal di Instagram. Penelitian ini bertujuan untuk mengukur keotentikan, integritas, konsistensi, spesialisasi, relevansi, visibilitas, persistensi, dan goodwill dari personal branding Danise Julia Francise Ratag. Metode kuantitatif deskriptif digunakan dengan menyebarkan kuesioner online kepada pengikutnya. Total responden pada penelitian ini adalah 100 orang. Teknik pengambilan sampel menggunakan teknik purposive sample. Teknik analisis data menggunakan program SPSS untuk mengukur variabel dan memberikan wawasan bagi individu yang tertarik membangun personal branding melalui instagram. Hasil penelitian menunjukkan bahwa Danise berhasil membangun personal branding yang autentik dan sesuai dengan identitasnya, serta mempertahankan integritas dan konsistensi dalam menyampaikan nilai-nilai yang relevan dengan bidang fashion. Kontennya dinilai relevan dengan tren terkini dan memiliki dampak positif yang kuat terhadap pengikutnya. Danise juga efektif dalam mengelola visibilitasnya di Instagram melalui penggunaan hashtag dan kolaborasi strategis, serta konsisten dalam menciptakan konten berkualitas yang mendukung interaksi intensif dengan pengikutnya. Implikasi dari penelitian ini adalah pentingnya mengoptimalkan strategi personal branding di platform Instagram.